The rights of children on the move in Indonesia : implementation and challenges - Shahnaz, Liza; Muhja, Zainal Abidin (Penerbit Universiti Kebangsaan Malaysia, 2022)
For decades ago, children have migrated for various reasons, such as avoiding conflict and persecution in their home countries, leaving poverty, seeking a better life in another country, uniting families who had already been in another country, and other reasons. Currently, children are a huge part of population movements. Soon, children will be positively affected due to globalization, socio-economic life changes, and natural changes. Although there is increasing attention to these migrated children’s fate, there has not yet been a complete legal instrument or other policies to protect these children’s fundamental rights while in Indonesia. This research aims to map the framework of fulfilling the rights of children on the move in the Indonesian constitution and its implementation and challenges. This research is essential considering that Indonesia is one of the parties to the 1989 Convention on the Rights of the Child (CRC), which requires each state-party to fulfil children’s rights regardless of national status, immigration status, and completeness of documents. This is a normative legal research with conceptual and statute approaches. The realization of these children’s rights is a benchmark for Indonesia’s commitment to obedience to international law obligations. The results show that Indonesia has been doing extra miles to fulfil the rights of children on the move, especially their educational and health rights.